2004
DOI: 10.1016/j.ydbio.2004.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Djeyes absent ( Djeya ) controls prototypic planarian eye regeneration by cooperating with the transcription factor Djsix-1

Abstract: A conserved network of nuclear proteins is crucial to eye formation in both vertebrates and invertebrates. The finding that freshwater planarians can regenerate eyes without the contribution of Pax6 suggests that alternative combinations of regulatory elements may control the morphogenesis of the prototypic planarian eye. To further dissect the molecular events controlling eye regeneration in planarians, we investigated the role of eyes absent (Djeya) and six-1 (Djsix-1) genes in Dugesia japonica. These genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 44 publications
3
71
0
Order By: Relevance
“…Since the initial characterization of the Pax6 gene, we have continued the search for planarian orthologs of genes involved in eye determination (Table 1). We confirmed that the initial eye genetic network is highly conserved in planarians compared to other metazoans, with the characterization of orthologs of sine oculis, eyes absent and opsin genes in different planarian species (Mannini et al, 2004. Loss of function of sine oculis and eyes absent confirms their function in eye determination during regeneration and maintenance in adult planarians (Fig.…”
Section: The Eye Genetic Networksupporting
confidence: 81%
See 2 more Smart Citations
“…Since the initial characterization of the Pax6 gene, we have continued the search for planarian orthologs of genes involved in eye determination (Table 1). We confirmed that the initial eye genetic network is highly conserved in planarians compared to other metazoans, with the characterization of orthologs of sine oculis, eyes absent and opsin genes in different planarian species (Mannini et al, 2004. Loss of function of sine oculis and eyes absent confirms their function in eye determination during regeneration and maintenance in adult planarians (Fig.…”
Section: The Eye Genetic Networksupporting
confidence: 81%
“…Loss of function of sine oculis and eyes absent confirms their function in eye determination during regeneration and maintenance in adult planarians (Fig. 5A, B) (Mannini et al, 2004, Pineda et al, 2000. Also, the production of transgenic planarians carrying several dimeric Pax6 binding sites plus an enhanced green fluorescent protein reporter gene produces a new phenotype in which the planarians show green eyes (Fig.…”
Section: The Eye Genetic Networkmentioning
confidence: 56%
See 1 more Smart Citation
“…Negative controls were carried out by injection of water, or 尾-Gal dsRNA or Djeya dsRNA. Djeya dsRNA was obtained as described by Mannini et al (Mannini et al, 2004). Intact specimens were injected three times, one injection every 2 days, for a week, then transected and allowed to regenerate.…”
Section: Rnai Experimentsmentioning
confidence: 99%
“…About 10 10 -10 11 molecules of dsRNA were injected in each specimen with a Nanoject microinjector apparatus (Drummond). Injections schedule was as reported in Mannini et al (2004). Amputated fragments were analyzed during the second round of regeneration.…”
Section: Djhsp90(rnai)mentioning
confidence: 99%